A review of CO2 and associated carbon dynamics in headwater streams: A global perspective. (28th June 2017) - Marx, A.; Dusek, J.; Jankovec, J.; Sanda, M.; Vogel, T.; van Geldern, R.; Hartmann, J.; Barth, J. A. C.
Abstract: Terrestrial carbon export via inland aquatic systems is a key process in the global carbon cycle. It includes loss of carbon to the atmosphere via outgassing from rivers, lakes, or reservoirs and carbon fixation in the water column as well as in sediments. This review focuses on headwater streams that are important because their stream biogeochemistry directly reflects carbon input from soils and groundwaters. Major drivers of carbon dioxide partial pressures ( p CO2 ) in streams and mechanisms of terrestrial dissolved inorganic, organic and particulate organic carbon (DIC, DOC, and POC) influxes are summarized in this work. Our analysis indicates that the global river average p CO2 of 3100 ppmV is more often exceeded by contributions from small streams when compared to rivers with larger catchments (> 500 km 2 ). Because of their large proportion in global river networks (> 96% of the total number of streams), headwaters contribute large—but still poorly quantified—amounts of CO2 to the atmosphere. Conservative estimates imply that globally 36% (i.e., 0.93 Pg C yr −1 ) of total CO2 outgassing from rivers and streams originate from headwaters. We also discuss challenges in determination of CO2 sources, concentrations, and fluxes. To overcome uncertainties of CO2 sources and its outgassing from headwater streams on the global scale, new investigations are needed that should include groundwater data. Such studies would also benefit from applications of integral CO2 outgassing isotope approaches and multiscale geophysical imaging techniques. Key Points: In terms of carbon fluxes, high cumulative contributions of headwater streams are currently underrepresented in the global carbon cycle Representative quantification of carbon dioxide outgassing from headwater streams on a global scale is an important future challenge A global analysis of small catchment chemistry revealed substantial influences of trace carbonate weathering on stream carbon budgets